Gambaran Tingkat Pengetahuan Orang Tua tentang Penyakit Tuberkulosis pada Anak di Poliklinik Anak Rumah Sakit Umum Daerah Sanjiwani Kabupaten Gianyar: Overview of Parental Knowledge Levels Regarding Tuberculosis in Children at the Pediatric Clinic of Sanjiwani General Hospital, Gianyar Regency - Ariesta, Gusti Ayu Viorya Ganes; Purnamayanti, Ni Made Dwi; Rahyani, Ni Komang Yuni (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2024)
ABSTRACT Background: Tuberculosis (TB) is a chronic infectious disease caused by the bacterium Mycobacterium Tuberculosis. Children are at high risk of developing illness after being infected and suffering from serious TB disease (TB meningitis, miliary TB). Latent TB infection in children, if not treated properly, will become a TB case in adulthood, which is a new source of transmission. In controlling childhood TB, parental knowledge is very necessary. Objective: To determine the level of knowledge of parents about tuberculosis in children at the Children's Polyclinic at Sanjiwani Regional General Hospital, Gianyar Regency. Method: This type of research is quantitative with a cross-sectional descriptive approach. The research was carried out in February-March 2024. The sampling technique used a non-probability sampling method, namely consecutive sampling. The sample consisted of 65 children suspected of having TB. Collecting data by distributing questions. Data analysis uses univariate in the form of frequency distribution. Results: Of the ten indicators, the respondents who mostly knew about the symptoms of TB in children were 83.1% and TB screening in children was 81.5%, while the respondents who mostly did not know about the pathogenesis of TB in children were 80.0% and treatment of TB disease in children was 67.7%. Conclusion: This research shows that the level of knowledge of parents about TB disease in children is mostly lacking, especially most do not know about pathogenesis and treatment. Suggestions: Health workers are expected to be able to carry out outreach with the health promotion team at the hospital, future researchers are expected to be able to develop descriptive research into relationship research, and parents are expected to be able to increase knowledge about TB disease in children to protect children from the threat of TB disease. Keywords: Level of Knowledge; Parents; Tuberculosis in Children